The Influence of Parenting Styles on Early Childhood Social Skills - Nurus Shofa Sitorus; Nurhafizah Nurhafizah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Developing a children's social skills from an early age will help build a rational thinking process and be able to make good decisions in the future. They will also understand themselves and others. This study aims to describe the family factors that trigger a child to have a lack of social skills. This research was conducted to examine and find out more and discuss the factors of parenting patterns that are closely related to children's social skills. This research describes qualitatively according to the type of case study against the background of 2 group B children aged 5-6 years having problems with their social skills, located in an RA in Tebing-Tinggi city. The type of research used in this study is qualitative descriptive with an approach. Children who lack social skills are likely to be rejected by their peers. Parents and teachers play an important role in directing children to socialize with others. Then, the intervention form includes playing solitaire, playing as an observer, playing parallel, playing associative, playing cooperative, and various forms of traditional games.